Gas exchange, chlorophyll and nutrient contents in relation to Na + and Cl − accumulation in ‘Sunburst’ mandarin grafted on different rootstocks - Garcı́a-Sánchez, Francisco; Jifon, John L.; Carvajal, Micaela; Syvertsen, James P. (Plant science (Limerick), 2002)
We investigated effects of salinity on the growth and net gas exchange of CO 2 and water vapour in leaves of 2-year-old ‘Sunburst’ mandarin [( Citrus reticulata Blanco)×( Citrus paradisi Macf.× C. reticulata)] trees grafted on either Cleopatra mandarin ( C. reticulata) or Carrizo citrange ( Citrus sinensis L. Osb.× Poncirus trifoliata L.) rootstocks. Trees were grown in a greenhouse and watered with a complete nutrient solution containing 0, 30, 60 or 90 mM NaCl. After 6 weeks of treatment, tree growth, net gas exchange of leaves, leaf chlorophyll and mineral nutrient concentration were measured. Salinity decreased growth and net gas exchange of leaves on all trees. Cleopatra roots accumulated higher concentrations of Cl − and Na + than Carrizo roots but ‘Sunburst’ leaves on Cleopatra accumulated less Cl − and Na + and had higher CO 2 exchange rates than those on Carrizo. This corresponded to higher concentrations of leaf N and chlorophyll in leaves of trees on Cleopatra than on Carrizo. Salinity increased N and decreased K + contents in roots of both rootstocks. Salinity increased N and decreased K + concentrations in leaves of trees on Cleopatra but not in trees on Carrizo. Salinity also increased Ca 2+ concentration and reduced Mg 2+ in leaves on Cleopatra. The lower Cl − and Na + concentration in leaves of ‘Sunburst’ grafted on Cleopatra than on Carrizo, suggests that the salinity tolerance of Cleopatra is associated with ion sequestration in roots with less transport to leaves.